Performance and reward practices of multinational corporations operating in Australia. (April 2015) - Bartram, Timothy; Boyle, Brendan; Stanton, Pauline; Sablok, Gitika; Burgess, John
This paper examines the performance management and reward practices of multinational corporations operating in Australia. Drawing on a representative sample of 211 multinational corporations, we examine the uptake and determinants of performance management and reward practices used by multinational corporations in Australia. We investigate the influence of established contextual and organisational factors on performance management and rewards and explore the use of such practices amongst managers relative to the largest occupational group. Our findings suggest that overall multinational corporations operating in Australia use a wide range of performance management and reward practices. Findings indicate that multinational corporations are higher users of such practices for managers relative to the largest occupational group. Logistic regression results demonstrate that multinational corporations with higher use of human resource-shared services and global human resource integration are more likely to use the measured performance management and reward practices for both the largest occupational group and managers, suggesting some level of global integration around human resource activities. There is also greater likelihood of the use of these practices where there is low union recognition for the purpose of collective bargaining for the largest occupational group. The implications of these findings are discussed.